2021
DOI: 10.1186/s43055-020-00400-1
|View full text |Cite
|
Sign up to set email alerts
|

A review on chest CT scanning parameters implemented in COVID-19 patients: bringing low-dose CT protocols into play

Abstract: Background This study aims to review chest computed tomography (CT) scanning parameters which are utilized to evaluate patients for COVID-19-induced pneumonia. Also, some of radiation dose reduction techniques in CT would be mentioned, because using these techniques or low-dose protocol can decrease the radiation burden on the population. Main body Chest CT scan can play a key diagnostic role in COVID-19 patients. Additionally, it can be useful to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…The accuracy in this study was also high but did not exceed that of Bahrami-Motlagh et al (96.6%) [20]. The CT sensitivity also in this study exceeded that in Azadbakht et al [25] (60-70%).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The accuracy in this study was also high but did not exceed that of Bahrami-Motlagh et al (96.6%) [20]. The CT sensitivity also in this study exceeded that in Azadbakht et al [25] (60-70%).…”
Section: Discussionsupporting
confidence: 50%
“…Summary of statistical results for "low-dose" and "ultra-low-dose" CT protocols in patients (< 80-kg body weight) 93% 90 25. to 94.92% 92.93% 90.25 to 94.92% 92.93% 90.25 to 94.92% 92.93% 90.25 to 94.92% Negative predictive value (NPV) 40.00% 11.31 to 77.70% 40.00% 11.31 to 77.70% 40.00% 11.31 to 77.70% 40.00% 11.31 to 77.70% 38% 83.03 to 95.29% 90.38% 83.03 to 95.29% 90.38% 83.03 to 95.29% 90.38% 83.03 to 95.29%…”
mentioning
confidence: 99%
“…The International Atomic Energy Agency (IAEA) organized a webinar to discuss CT practice and protocols for COVID-19 from a radiation protection perspective [10]. The median CT dose index for chest CT was 9 mGy in COVID-19 pneumonia as summarized from 782 patients from 54 health care sites in 28 countries, which has eightfold variations across multiple health care sites and is deemed as regular dose [11]. For example, Pan et al reported CTDIvol of 8.4 ± 2.0 mGy for single chest CT exam of COVID-19 patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…Chest CT has been and is continuing to be the most widely implemented imaging modality to diagnose COVID-19 pneumonia and in some cases triage patients throughout the globe. Even low-dose chest CT scan is capable of diagnosing COVID-19 pneumonia accurately [ 15 ]. All common CT patterns of COVID-19 pneumonia have been reported and discussed thoroughly in literature.…”
Section: Discussionmentioning
confidence: 99%